Analisis Desain Tembok Penahan Tanah Desa Panemon - Sugihwaras - Bojonegoro - Mohammad Zainul Ikhwan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Panemon Village is an area with soil conditions prone to landslides on the Lunto Rice Field road. This location is an alternative road that connects Sugihwaras District and Temayang District. During the rainy season the slopes are prone to landslides, thus disrupting traffic and causing danger to local residents. So it is necessary to construct a retaining wall structure to withstand lateral earth pressure caused by the fill soil due to topographical conditions as well as other additional loads. This study plans cantilever type retaining walls and sheet piles. aims to determine the value of safe safety, to withstand soil slides, to determine the value of stability against shear and overturning and the value of stability against collapse of soil carrying capacity, using the theory of Rangkine and Tarzaghi. The results showed that the dimensions of the cantilever type with dimensions H = 4.5 m, B = 2.25 m had a safety factor value for external stability overturning force 22.26 > 2.0, shear 2.57 > 1.5 with soil cohesion of 0.85, the angle of friction of the soil is 59.0°, the unit weight of the soil is 1.85, so the carrying capacity of the soil is 2984.65 greater than the soil stress under the wall qtoe = 2.36 and qheels = 47.70.